Inhaled mRNA Nanoformulation with Biogenic Ribosomal Protein Reverses Established Pulmonary Fibrosis in a Bleomycin‐Induced Murine Model (Adv. Mater. 14/2022). Issue 14 (7th April 2022) - Zhang, Rui; Jing, Weiqiang; Chen, Chen; Zhang, Shengchang; Abdalla, Mohnad; Sun, Peng; Wang, Ganyu; You, Wenjie; Yang, Zhenmei; Zhang, Jing; Tang, Chunwei; Du, Wei; et al.
Abstract : Nanomedicine In article number 2107506, Xinyi Jiang and co‐workers introduce an inhaled nanoformulation that is developed with biogenic ribosomal protein for mRNA delivery. The variety of isoelectric points of ribosomal proteins endows them with flexible positive charge properties, by which negatively charged mRNA is efficiently condensed to form a nanocomplex in a biomimetic fashion.